2022
DOI: 10.1249/mss.0000000000003103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Cuff Pressure on Physiological Responses during Blood Flow Restriction Resistance Exercise in Young Adults

Abstract: PurposeThe purpose of this study was to examine the physiological responses resulting from an acute blood flow restriction resistance exercise bout with two different cuff pressures in young, healthy men and women.MethodsThirty adults (18–30 yr) completed a bilateral leg extension blood flow restriction bout consisting of four sets (30–15–15–15 repetitions), with cuffs applied at pressures corresponding to 40% and 60% of the minimum arterial occlusion pressure (AOP) needed to completely collapse the femoral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…the BFR pressure applied which has been demonstrated to alter the physiological responses [41,43] and discomfort (e.g., higher pressures result in greater discomfort). Therefore, it is imperative that TAOP is determined accurately and precisely.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…the BFR pressure applied which has been demonstrated to alter the physiological responses [41,43] and discomfort (e.g., higher pressures result in greater discomfort). Therefore, it is imperative that TAOP is determined accurately and precisely.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Specifically, the safety and effectiveness of BFR exercise has been routinely demonstrated with the implementation of the standard 75 repetition (1 × 30, 3 × 15) scheme [28,40]. Additionally, the exercise is performed at 30 % of 1RM (i. e., a low weight/ resistance) and with the small, inflated cuff set to a pressure corresponding to 40-80 % of arterial occlusion pressure (i. e., approximately 40-80 % of systolic blood pressure) [41,42].…”
Section: Innovation Applications To Determine Blood Flow Restriction ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of sex differences in microvascular function continue to garner substantial interest, 1–5 especially findings resulting from vascular occlusion tests (VOT) in which near‐infrared spectroscopy (NIRS) devices are used to assess skeletal muscle tissue oxygenation (StO 2 , %) 6–9 . Related to NIRS‐VOT, previous data from our laboratory, 6 as well as from others, 8 have indicated that following transient ischemia, males exhibit faster rates of reoxygenation and greater maximal values (StO 2max ) than females.…”
Section: Introductionmentioning
confidence: 99%